2016
DOI: 10.1016/j.vaccine.2016.02.038
|View full text |Cite
|
Sign up to set email alerts
|

Immunisation with proteins expressed during chronic murine melioidosis provides enhanced protection against disease

Abstract: a b s t r a c tThere is an urgent need for an effective vaccine against human disease caused by Burkholderia pseudomallei, and although a wide range of candidates have been tested in mice none provide high level protection. We considered this might reflect the inability of these vaccine candidates to protect against chronic disease. Using Q-RT PCR we have identified 6 genes which are expressed in bacteria colonising spleens and lungs of chronically infected mice. Three of the genes (BPSL1897, BPSL3369 and BPSL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…14 The humanized NOD/SCID/Jak3 null mouse model can receive PBMCs from seropositive donors as it completely lacks T, B, NK and NKT cell functions. [13][14][15][16]49,50 Here, we show that the IFN-c response from PBMCs from seropositive individuals living in a melioidosis endemic area, upon stimulation with B. pseudomallei antigens, is significantly greater than in PBMCs from seronegative individuals. [13][14][15][16]49,50 Here, we show that the IFN-c response from PBMCs from seropositive individuals living in a melioidosis endemic area, upon stimulation with B. pseudomallei antigens, is significantly greater than in PBMCs from seronegative individuals.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…14 The humanized NOD/SCID/Jak3 null mouse model can receive PBMCs from seropositive donors as it completely lacks T, B, NK and NKT cell functions. [13][14][15][16]49,50 Here, we show that the IFN-c response from PBMCs from seropositive individuals living in a melioidosis endemic area, upon stimulation with B. pseudomallei antigens, is significantly greater than in PBMCs from seronegative individuals. [13][14][15][16]49,50 Here, we show that the IFN-c response from PBMCs from seropositive individuals living in a melioidosis endemic area, upon stimulation with B. pseudomallei antigens, is significantly greater than in PBMCs from seronegative individuals.…”
Section: Discussionmentioning
confidence: 64%
“…13,14 Furthermore, some of these proteins have been shown to induce the production of IFN-c, a key cytokine with an established role in protection against 14 Some antigens have been further studied in vivo. 16 Another seroreactive antigen candidate that has been tested in vivo is flagellin (FliC; BPSL3319), which has been shown to trigger IFN-c responses from human T cells, and antibodies raised against FliC have been shown to protect mice in passive immunization trials. 15 Recently, a multi-antigen formulation containing BPSL2765, in combination with three other chronicphase-associated antigens, was found to offer enhanced protection against mice challenged with B. pseudomallei.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps a more in-depth analysis of epitopes could provide knowledge that will allow researchers to design better antigens that improve immunogenicity, with the potential to provide protection over the course of long-term infection. The work of Champion et al, evaluating expression markers in the bacteria of chronically infected mice [58] is a step in the right direction to create vaccines to combat long-term infection, approaching the problem as an immunologist rather than a microbiologist could further lead new information on vaccine improvement. A collaborative effort from microbiologists and immunologists, as well as vaccine formulation scientists, could work to overcome this difficult-to-prevent infection.…”
Section: Discussionmentioning
confidence: 99%
“…B. pseudomallei challenge following subcutaneous immunization [57]. More recently, Champion et al, identified a series of genes: BPSL1897 (uncharacterized protein), BPSL3369 (acetaldehyde dehydrogenase), and BPSL2287 (iron cluster assembly protein) expressed by the bacteria colonizing the spleens and lungs of chronically infected mice [58]. Following co-administration with these recombinant proteins and MPL, significant protection was observed for 42 days against lethal challenge [58].…”
Section: Subunit Vaccinesmentioning
confidence: 99%
“…These proteins are known to stimulate a T-cell-dependent immune response, resulting in T-cell and B-cell memory, along with antibody affinity and isotype switching (9,10). In fact, previous studies have shown that proteins alone can provide significant, albeit incomplete, protection against Burkholderia challenge (11)(12)(13)(14). However, more recent studies have shown that when immunogenic proteins are incorporated in a glycoconjugate vaccine in conjunction with the highly antigenic Burkholderia lipopolysaccharide (LPS) or capsular polysaccharide (CPS), a more robust immune response is generated (15)(16)(17)(18).…”
mentioning
confidence: 99%